2017
DOI: 10.3762/bjoc.13.186
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of small organic molecules

Abstract: With the growing interest in renewable energy and global warming, it is important to minimize the usage of hazardous chemicals in both academic and industrial research, elimination of waste, and possibly recycle them to obtain better results in greener fashion. The studies under the area of mechanochemistry which cover the grinding chemistry to ball milling, sonication, etc. are certainly of interest to the researchers working on the development of green methodologies. In this review, a collection of examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(117 citation statements)
references
References 192 publications
0
116
0
1
Order By: Relevance
“…An important incentive to study mechanochemical phenomena is their potential usefulness for making new materials and to make current or future technologies more efficient . As the demand for better recovery, higher efficiency, and greener operation increases, interest in the use of mechanical activation will grow …”
Section: Introductionmentioning
confidence: 99%
“…An important incentive to study mechanochemical phenomena is their potential usefulness for making new materials and to make current or future technologies more efficient . As the demand for better recovery, higher efficiency, and greener operation increases, interest in the use of mechanical activation will grow …”
Section: Introductionmentioning
confidence: 99%
“…Polyvalent iodine derivatives are versatile reagents for C–N bond constructions [4,6]. Mechanochemical conditions such as ball milling are considered to be one of the premium techniques in solvent-free synthesis [7]. Under these conditions, maximum concentration is expected to put those systems under high stress and therefore violent exothermic reactions or even explosions may take place between hypervalent iodine reagents and electron-rich amines.…”
Section: Introductionmentioning
confidence: 99%
“…[5,10,14] It was shown that milling balls made from copper can act as catalyst, namely in the coupling of tetrahydroisoquinolines with nitroalkanes or the azide-alkynecycloaddition; in the latter case, also the copper milling jar was catalytically active. [5,10,14] It was shown that milling balls made from copper can act as catalyst, namely in the coupling of tetrahydroisoquinolines with nitroalkanes or the azide-alkynecycloaddition; in the latter case, also the copper milling jar was catalytically active.…”
Section: Apparatusmentioning
confidence: 99%
“…[4,5,[9][10][11][12] There are numerous reports on mechanochemical syntheses (stoichiometric and catalytic), which work already efficiently in solution and where mechanochemistry does not introduce a significant "synthetic" benefit, apart from avoiding the solvent. Useful summaries can be found in recent reviews.…”
Section: Mechanochemistry In Organic Synthesismentioning
confidence: 99%